2019
DOI: 10.1002/ehf2.12500
|View full text |Cite
|
Sign up to set email alerts
|

Differences in blood pressure riser pattern in patients with acute heart failure with reduced mid‐range and preserved ejection fraction

Abstract: AimsHeart failure (HF) is classified into three types according to left ventricular ejection fraction (EF). The effect of blood pressure (BP) on the pathogenesis of each type is assumed to be different. However, the association between the prognosis of each type of HF and abnormal BP variations assessed by ambulatory BP monitoring (ABPM), such as nocturnal hypertension and the riser pattern, remains unclear.Methods and resultsWe studied 325 consecutive patients with decompensated HF who were acutely admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 38 publications
2
19
0
2
Order By: Relevance
“…We also conducted another study in patients with ADHF, known as the Nara Registry and Analyses for Heart Failure cohort study (NARA-HF study). NARA-HF study found that 31% of patients with a history of AMI were classified as HFpEF, 13 supporting the present findings on the frequency of HFpEF after AMI. In contrast, only 18% of patients with HFpEF CI, confidence interval.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also conducted another study in patients with ADHF, known as the Nara Registry and Analyses for Heart Failure cohort study (NARA-HF study). NARA-HF study found that 31% of patients with a history of AMI were classified as HFpEF, 13 supporting the present findings on the frequency of HFpEF after AMI. In contrast, only 18% of patients with HFpEF CI, confidence interval.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies, which investigated the frequency of HF and mortality following AMI using electronic health records, showed that approximately 16–24% of patients with a history of AMI were rehospitalized during the 3–4 year follow‐up after index hospitalization 10,11 . Conversely, the current registries of acute decompensated HF (ADHF) report that approximately 7.5–25% of patients have a history of AMI 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…Decreased stroke volume cannot maintain sufficient blood that ABPM had prognostic significance even during hospitalization. 26 Second, the doses of antihypertensive medications and the timing of drug administration could influence MBPS. However, multiple drugs are usually prescribed to HF patients.…”
Section: Hemodynamic Effects Of Mbpsmentioning
confidence: 99%
“…Some studies recently found that the subgroup of patients with HFpEF and the night-time riser pattern of blood pressure, as determined ambulatory blood pressure monitoring, was at higher risk for CV events and HHF. 39 , 40 The use of SGLT2 inhibitors may be more promising in these patients, because these drugs likely reduce night-time blood pressure in patients with T2D and uncontrolled nocturnal hypertension. 41…”
Section: Discussionmentioning
confidence: 99%